A new category of autoinflammatory disease associated with NOD2 gene mutations - Yao, Qingping (BioMed Central, 2011)
INTRODUCTION: Autoinflammatory diseases are characterized by seemingly unprovoked episodes of inflammation, without high titers of autoantibodies or antigen-specific T cells, and derive from genetic variants of the innate immune system. This study characterized a cohort of patients with similar phenotypes and nucleotide oligomerization domain 2 (NOD2) gene mutations. METHODS: Diagnostically challenging patients with the following clinical and genetic characteristics were prospectively studied between January 2009 and April 2011: periodic fever, dermatitis, polyarthritis, serositis, negative serum autoantibodies and additional positive NOD2 IVS8(+158 )gene mutation. Genetic testing for gene mutations of NOD2, tumor necrosis factor receptor-associated periodic fever syndrome (TRAPS) and familial Mediterranean fever (FMF) was performed. RESULTS: All seven patients with the disease were Caucasians, with four being male. The mean age at disease onset was 40.7 years and disease duration was 3.2 years. These patients characteristically presented with periodic fever, dermatitis and inflammatory polyarthritis. There were gastrointestinal symptoms in three patients, granulomas of the skin and gut in two, and recurrent chest pain in two, with one having pleuritis and pericarditis. Three patients had sicca-like symptoms. Five patients had increased acute phase reactants. All seven patients had negative tests for autoantibodies but carried the NOD2 gene mutation IVS8(+158 )with four having concurrent R702W mutation. CONCLUSIONS: Our cohort may represent a new disease category of autoinflammatory disease with characteristic clinical phenotypes and genotypes. It may somewhat resemble pediatric Blau's syndrome.